Human liver flukes in China and ASEAN: Time to fight together - Qian, Men-Bao; Zhou, Xiao-Nong (PLoS neglected tropical diseases, 2019)
In particular, only three parasites are definite carcinogens, including both C. sinensis and O. viverrini [7], which are responsible for a conservative estimate of 7,000 new cases of cholangiocarcinoma yearly [8]. [...]China and ASEAN member countries are highly afflicted with cholangiocarcinoma [9]. [...]research and development on liver flukes have already achieved some breakthroughs in different countries—e.g., mapping and surveillance in China, drug development in China and Laos, the carcinogenic mechanism, diagnosis and management of cholangiocarcinoma in Thailand, and the management of aquaculture in Vietnam [14–19]. [...]there exist good cooperative platforms, such as the Regional Network for Asian Schistosomiasis and other Helminth Zoonoses (RNAS+), of which all countries endemic for clonorchiasis and opisthorchiasis viverrini are members [20]. First report and molecular identification of Opisthorchis viverrini infection in human communities from Lower Myanmar.